Enlarged Virchow-Robin Spaces in A Young Man: A Constrained Spherical Deconvolution Tractography Study - Cacciola, Alberto; Calabrò, Rocco Salvatore; Costa, Antonio; Naro, Antonino; Milardi, Demetrio; Bruschetta, Daniele (Acta Biomedica Atenei Parmensis, 2017)
Background and aim: Virchow-Robin spaces are mainly located along the path of the lenticulo-striate arteries in the basal ganglia through the anterior perforate substance, and can be found both in normal subjects, as a rare phenomenon, and in patients with different diseases. We report a case of a healthy young man with unilateral enlarged Virchow-Robin spaces in the left capsule-lenticulostriate area. Aim of this case report is to show the potential of probabilistic Constrained Spherical Deconvolution (CSD) tractography in showing abnormal diffusion tensor imaging and tractography of the anterior thalamic tracts caused by mass effect from adjacent enlarged Virchow-Robin spaces. Methods: The study was performed with a 3T magnetic resonance imaging (MRI) scanner (Achieva, Philips Healthcare, Best, Netherlands); equipped with a 32-channel SENSE head coil. Diffusion Weighted Images were analyzed by using CSD, a fast computation method that overcomes major limitations of Diffusion Tensor Imaging allowing reliable estimation of one or more fiber orientations in the presence of intravoxel orientational heterogeneity. Results: Tractography showed increased Fractional Anisotropy and reduced Apparent Diffusion Coefficient values, a displacement and compression of the anterior thalamic projections by part of the enlarged VRS, and a decrease of white matter fibers in the left side in comparison to the right one. Conclusions: We report on a case of a healthy individual with unilateral dilated VRS in the capsulo-lenticulostriatal area, proving the utility of diffusion MRI and tractography in understanding the abnormal neuroanatomy of this particular condition.